(β‐D‐Ribofuranosyl)formamidine in the Design and Synthesis of 2‐(β‐D‐Ribofuranosyl)pyrimidines, Including RF‐Containing Derivatives. Issue 15 (4th April 2013) - Iaroshenko, Viktor O.; Dudkin, Sergii; Sosnovskikh, Vyacheslav Ya.; Villinger, Alexander; Langer, Peter
Abstract: A wide range of novel 2‐(β‐D ‐ribofuranosyl)pyrimidines, including R F ‐containing derivatives, have been synthesized by the reaction of (β‐D ‐ribofuranosyl)formamidine with various dielectrophilic substrates such as 3‐alkoxy‐ and 3‐chloro‐1‐(polyfluoroalkyl)propen‐1‐ones, 3‐nitro‐ and 3‐(phenylethynyl)chromones and heteroaryl acetylenic ketones. Abstract : Polyfluoroalkyl‐containing 2‐(β‐D ‐ribofuranosyl)pyrimidine derivatives have been synthesized by the reaction of (β‐D ‐ribofuranosyl)formamidine with dielectrophilic substrates such as 3‐alkoxy‐ and 3‐chloro‐1‐(polyfluoroalkyl)propen‐1‐ones, 3‐nitro‐ and 3‐(phenylethynyl)chromones and heteroaryl acetylenic ketones.